1992
DOI: 10.1002/j.1460-2075.1992.tb05472.x
|View full text |Cite
|
Sign up to set email alerts
|

The cooperative binding of fructose-1,6-bisphosphate to yeast pyruvate kinase.

Abstract: The cooperative binding of the allosteric activator fructose‐1,6‐bisphosphate [Fru(1,6)P2] to yeast pyruvate kinase was investigated by equilibrium dialysis and fluorescence quench titration. The results show that yeast pyruvate kinase binds four molecules of Fru(1,6)P2 per tetramer and the observed fluorescence quench follows the binding of the ligand and not the cooperative T to R state transition. Additionally it is shown that the binding of Fru(1,6)P2 to yeast pyruvate kinase is compatible with the model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…At the low F1,6bP 2 concentrations prevailing during gluconeogenic conditions, the enzyme showed cooperativity with respect to phosphoenolpyruvate. At high F1,6bP 2 concentrations, however, the enzyme exhibited hyperbolic Michaelis±Menten kinetics with increased affinity for phosphoenolpyruvate, in line with earlier findings [92,93]. We found that the activation is maximal at 0.5 mm of F1,6bP 2 , which is more than 10 times lower than the concentration that we have measured.…”
Section: Pyruvate Kinase: Pyksupporting
confidence: 92%
“…At the low F1,6bP 2 concentrations prevailing during gluconeogenic conditions, the enzyme showed cooperativity with respect to phosphoenolpyruvate. At high F1,6bP 2 concentrations, however, the enzyme exhibited hyperbolic Michaelis±Menten kinetics with increased affinity for phosphoenolpyruvate, in line with earlier findings [92,93]. We found that the activation is maximal at 0.5 mm of F1,6bP 2 , which is more than 10 times lower than the concentration that we have measured.…”
Section: Pyruvate Kinase: Pyksupporting
confidence: 92%
“…For example, the observed decrease in the intracellular trehalose-6-phosphate concentration was consistent with a gradual release of the inhibition of HXK by this metabolite (4). Similarly, the metabolite profiles for fructose-2,6-bisphosphate and fructose-1,6-bisphosphate are likely to have contributed to the activation of PFK and PYK, respectively (3,25).…”
Section: Discussionmentioning
confidence: 61%
“…For example, it has been shown that high glucose concentrations result in modification of V max by transcriptional repression of HXK1 and ADH2 (12) and also by covalent modification of enzymes (e.g., via the phosphorylation of Pyk1, Pyk2, and Hxk2 [28]). A sudden glucose excess also results in major changes in metabolite concentrations that, in turn, affect the in vivo activity of key enzymes, such as HXK (inhibited by trehalose-6-phosphate [4]), PFK (activated by fructose-2,6-bisphosphate [3]), and PYK (activated by fructose-1,6-bisphosphate [25]). …”
mentioning
confidence: 99%
“…Most probably, the main control of the glycolytic rate in the mutant strain(s) is exerted by the sugar uptake system (8), but other control mechanisms may be operative as well. For instance, the low concentration of FBP may contribute, since this is a known allosteric activator of the pyruvate kinase reaction (15,21,23). However, the identity of the initial glucose repression signal(s) will be further elucidated by the use of the TM6* strains and other strains covering a range of glycolytic rates at high external sugar concentrations (8).…”
Section: Discussionmentioning
confidence: 99%